2014
DOI: 10.1007/s40415-013-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

Habitat filtering and interspecific competition influence phenological diversity in an assemblage of Neotropical savanna grasses

Abstract: Phenology in plants is closely related to the environmental features of their habitats, which can act as habitat filtering, clustering species with particular adaptations. On the other hand, aggregation of species can lead to competition between them, segregating their niches. We investigated if habitat filtering and interspecific competition influence phenological diversity in an assemblage of grass species in savanna grasslands of central Brazil. We conducted phenological observations, in 15-day intervals, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Grasses are among the dominant taxa in grassland and savanna physiognomies of the Cerrado Felfili, 2006, 2007a), and seeds of most species are likely to have PD (Ramos et al, 2016(Ramos et al, , 2017. Seed dispersal occurs in general from the middle of the wet season to the beginning of the dry season (Munhoz and Felfili, 2007b;Ramos et al, 2014).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Grasses are among the dominant taxa in grassland and savanna physiognomies of the Cerrado Felfili, 2006, 2007a), and seeds of most species are likely to have PD (Ramos et al, 2016(Ramos et al, , 2017. Seed dispersal occurs in general from the middle of the wet season to the beginning of the dry season (Munhoz and Felfili, 2007b;Ramos et al, 2014).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Through examining functional diversity metrics related to interand intraspecific variation in the Brazilian pampa forest community, Carlucci et al (2015) found that conspecific individuals varied more in communities where trait variability was typically high, that is, in the large forest patch, and less where trait variability was typically low, that is, in the small forest patches. Additionally, in Brazilian savannas, a phenological study showed that grasses are under competition pressure that can result in larger niche segregation, allowing coexistence between them (Ramos et al 2014).…”
Section: Internal Filteringmentioning
confidence: 99%
“…Another important trait to evaluate is longevity and the capacity of seeds to resist high temperatures since most fires in the Cerrado occur during the dry season (Ramos-Neto and Pivello, 2000;Pivello, 2011) and most grass species disperse during the rainy season (Munhoz and Felfili, 2007;Ramos et al, 2014). Therefore, dormant seeds are assumed to be in the seed bank when the fire occurs.…”
Section: Introductionmentioning
confidence: 99%